CORPORATE GOVERNANCE : DEMOGRAFI ORGANISASI, KARAKTERISTIK DEWAN DAN KINERJA PADA PERUSAHAAN YANG TERMASUK LQ 45 DI BURSA EFEK INDOENESIA - Muda Setia (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
The dimensions of good corporate governance can certainly affect the condition of the company, including LQ 45 Company. The LQ 45index is the value of the market capitalization of 45most liquid stocks and has a large capitalization value which is theliquidationindicator. LQ 45 index uses 45 selected stocks based on stock trade liquidity and adjusted every six months (every early February and August). LQ 45 index only consists of 45 selected stocks of various selection criteria, so it will be consisting of stocks with high liquidity and market capitalization. Thus, it is understandable that companies included in LQ45 areones with a good performance. However, theinfluence of good corporate governance implementation is not yet known through the demographic organization and characteristics of the board toward the company performance. Therefore, it is necessary to conduct further research related to good corporate governance in LQ 45 companies in the aspect of organization demography and the board’scharacteristics. This research was conducted to determine the relationship between organization demography and the characteristics of the board of directors toward the accounting performance (ROA and ROE) in LQ 45. Statistical analysis in this study is conducted by multiple linear regressions. The regression equation in this study is formulated into a model equation, as in the hypotheses and research framework model. In this study, 2 testing of multiple regression analysis were conducted. The regression equation for the first test is as follows. The results showed that: (1) there is a significant effect of organization demographyto the characteristics of the board, (2) there is a significant influence of the characteristics of the board on the performance of accounting, (3) there is no significant influence of the age of the organization to the characteristics of the board, (4 ) there is a significant positive influence of the size of the organization on the characteristics of the board, (5) there is no significant influence of the length of time the organization is listed on the Stock Exchange (BEI)to the characteristics of the board, (6) there is a significant positive influenceof the size of the board to the accountingperformance, (7) There is no significant influence of the CEO duality to the accountingperformance, (8) there is no significant influence of the independence of the CEO on the accountingperformance, (9) there is no significant influence of gender on the accounting performance